Faith, Fatherhood, and the Ethics of Care: Exploring Father–Daughter Relationships in South Africa - Swartz, Jesme Eugenie (Stellenbosch : Stellenbosch University, 2026)
Thesis (MA)--Stellenbosch University, 2026.